2023
DOI: 10.1371/journal.pone.0280896
|View full text |Cite
|
Sign up to set email alerts
|

Estimated pulse wave velocity as a measure of vascular aging

Abstract: Background Carotid-femoral pulse wave velocity (cfPWV), the referent measure of aortic stiffness, is an established measure of vascular aging. In studies where cfPWV cannot be measured, alternative methods are needed to help promote research on vascular aging. This study examines the construct validity of a measure of PWV estimated from age and blood pressure (ePWV). The specific aims of the study are to: 1) explore the strength of association between ePWV, cfPWV, and other established measures of vascular agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 46 publications
1
26
0
1
Order By: Relevance
“…ePWV predicts cardiovascular and cerebrovascular events and all-cause mortality independent of traditional CVD risk factors ( 15 , 19 21 , 40 , 42 47 ). Furthermore, they revealed that ePWV is linked to recognized indicators of vascular aging and could serve as a valuable tool for advancing research on vascular aging in their recent study by Heffernan KS et al ( 48 ). Therefore, ePWV could be a candidate for the initial assessment of arterial stiffness and the early identification of those at high risk.…”
Section: Discussionmentioning
confidence: 99%
“…ePWV predicts cardiovascular and cerebrovascular events and all-cause mortality independent of traditional CVD risk factors ( 15 , 19 21 , 40 , 42 47 ). Furthermore, they revealed that ePWV is linked to recognized indicators of vascular aging and could serve as a valuable tool for advancing research on vascular aging in their recent study by Heffernan KS et al ( 48 ). Therefore, ePWV could be a candidate for the initial assessment of arterial stiffness and the early identification of those at high risk.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that there is a strong association between ePWV and CfPWV (r=0.7) (36). Similarly, a recent study by Heffen et al showed that ePWV is associated with established indicators of vascular ageing such as carotid thickness, carotid stiffness and augmentation dilatation index (37). Therefore, ePWV may be a useful tool in the assessment of vascular aging.…”
Section: Perspectivesmentioning
confidence: 94%
“…The cfPWV is a gold standard for measuring arterial stiffness and is highly correlated with the ePWV (r ¼ 0.7) [41]. Studies have demonstrated a correlation between ePWV and established markers of vascular aging, including carotid thickness, carotid stiffness and augmentation dilatation index [42]. Although ePWV cannot completely replace cfPWV to assess arterial stiffness, ePWV has been shown to provide a robust predictive value as a 'gatekeeper' for all-cause mortality in different cohorts [43][44][45].…”
Section: Antihypertensivesmentioning
confidence: 99%